Inflation Targeting and Exchange Rate Regimes in Emerging Markets - Ebeke, Christian (IMF Working Papers; Working Paper, 2015)
This paper investigates the effects of the adoption of inflation targeting (IT) on the choice of exchange rate regime in emerging markets (EMs), conditional on certain macroeconomic conditions. Using a large sample of EMs and after controlling for the selection bias associated with the adoption of IT, we find that IT countries on average have a relatively more flexible exchange rate regime than other EMs. However, the flexibility of the exchange rate regime shows strong heterogeneity among IT countries depending on their degree of openness and exposure to FX risks. Moreover, we find that the marginal effect of IT adoption on the exchange rate flexibility increases with the duration of the IT regime in place, and with the propensity scores to adopt it.